Foreword - Daniel, Ana (2019)
Many universities across the world encourage entrepreneurship in ways that range from educational programs to the implementation of initiatives that support new companies’ creation. In the last decades, entrepreneurship education has grown on importance as an approach to prepare students, not only to become entrepreneurs and owners of an enterprise, but also to be able to chase opportunities and innovation as an employee and be a person who displays enterprising behaviour. This broad understanding of the aims of entrepreneurship education has stressed the need to rethink the pedagogical approaches used in classesin order to promote the development of non-cognitive skills, like creativity, persistence, self discipline, focus, teamwork, organization, staying on task and so on. Additionally, it has highlight the relevance of promoting an entrepreneurial ecosystem as a mean to potentiate the impact of entrepreneurship education.